New estimates of total factor productivity, technical and efficiency changes for the global agricultural economy - Le Clech, Néstor A.; Fillat-Castejon, Carmen (Spanish Journal of Agricultural Research, 2020)
Aim of study: The accuracy of international and intertemporal comparisons of total factor productivity (TFP) growth requires the use of indicators that satisfy transitive and multiplicative properties, such as the Färe-Primont index (FPI). This paper compares the evolution of TFP in global agriculture. Area of study: Worldwide. Material and methods: The evolution of TFP in global agriculture was measured by the traditional Malmquist index (MI) and by the FPI, with alternative measurements of input capital. Main results: We found a significantly lower TFP growth with the FPI. New estimates of TFP growth for 1961-2015 show that output oriented scale-mix efficiency drives TFP growth, with an important technological change between 1996 and 2000 and another in 2014. Regional comparisons reveal heterogeneous trends in efficiency, linked to institutional reforms and agricultural R&D. Research highlights: More realistic figures and global comparisons of agricultural productivity provide a better understanding to implement better policies. Available measures of capital stock do not yield significant differences in TFP estimations, but the precise identification and estimation of the heterogeneous drivers and burdens is fundamental for boosting agricultural productivity and its benefits on global food security.